Summary Proceedings of the First Annual Meeting of the Board of Governors 1946. (Summary Proceedings; 1st Annual Meeting, 1946, 1946)
This paper outlines that many countries have only begun to recover from the devastation of war; and the reconstruction of their economic and monetary systems will take several years. The wartime economic controls of many members of the IMF are still in force. Concrete measures for international economic cooperation, in spheres other than the financial, are not as far advanced as had earlier been hoped. International political cooperation leaves much to be desired. A number of countries, particularly in Europe and the Far East, find their international economic position seriously deteriorated as a result of the war. Their first task is to restore agricultural and industrial production on a modern and efficient basis and to bring it into line with the new requirements of the market. Although foreign aid has been of great assistance, it is important to recognize that recovery in the occupied countries has depended and will continue to depend primarily on their own efforts.